Beyond Blue. - Predd, P.P.
This paper presents the use of zinc oxide in UV emitting devices. It is a better material than gallium nitride for making these devices because it naturally emitts at those wavelengths more efficiently. The main hurdle to making zinc oxide devices has been getting stable - reliable p-type material material with an excess of holes, or electron deficiencies. Making an LED or laser diode requires a junction between p-type and n-type material. But when some of the zinc oxide is engineered to act as p-type material, it tends to revert to its natural n-type state after few months, which would cause a device to fail. This paper discusses some ways on how to make a p-type material
Keywords: LED; MOXtronics; UV emitting devices; University of Missouri; ZnO; Gallium nitride; Hybrid beam deposition; Laser diode; N-type material; P-type material; Pulsed laser deposition; Ultraviolet lasers; Zinc oxide